Readiness Assessment Model for implementation and Adoption of Knowledge Management at Iranian Post Company (Center of Information Technology) - Maryam Akhavan kharazian; Jamshid  Salehi sadaghiani; Masumeh Monafi (مطالعات مدیریت کسب و کار هوشمند, 2016)
Knowledge management is regarded as one of the strategic resources of competitive Advantage. One of the most fundamental issues in knowledge management is how to accept this approach. In this study, for identifying the factors of readiness of organizations for accepting knowledge management, first through studding the literature review, critical factors of knowledge management acceptance was identified from perspective of different global thinkers and experts. Then in order to make applied study, the presented models by knowledge management experts was reviewed and finally conceptual model of study was established. In this model, four critical factors as factors influencing on readiness for accepting knowledge management was identified. Then for each factor, evaluation criteria was extracted and established. For this purpose, for each of the related criteria with each of the factors, some questions were established and in format of Questionnaire were given to the organizational experts. And Exploratory Factor Analysis for enough assay of the sample statistical society is used. Also, for answer to main question and hypothesis certify used One Sample T-Test.